International origins of social and political theory - Lawson, George, active 2017; Barkawi, Tarak (Bingley : Emerald Publishing Limited, 2017)
This special issue is animated by the necessary entanglement of theory and history, the cortical relationship between theory and practice, and the transboundary (i.e. international) relations that help to constitute systems of thought and practice. We make three core arguments: first, all theory is situated knowledge, derived in and through history; second, theory-practice is a single field in which theory arises out of and acts upon historical experience; and third, both social and political theory have international origins - theory is forged through ongoing encounters between'here' and'there','home' and'abroad', and the'domestic' and the'foreign'.
Prelims -- The international origins of social and political theory -- The imperial origins of social and political thought -- The international origins of hannah arendt's historical method -- What kind of theory is the labor theory of value? Marx as genealogist in zur kritik --'These days of shoah' : history, habitus, and realpolitik in Jewish Palestine, 1942-1943 -- Late-Victorian worlds : Alfred Marshall on competition, character, and anglo-saxon civilization -- Epistemic ruptures : history, practice, and the anticolonial imagination -- Empire and violence : continuity in the age of revolution -- Superfluous injury and unnecessary suffering : national liberation and the laws of war -- The sovereign society : historical rupture and the emergence of the'domestic' in 17th century Europe and East Asia -- About the editors -- Index.
Includes index.
Keywords: Sociology; Social Science -- Sociology / Social Theory; Social theory